PENGARUH KEBIASAAN BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA MATA KULIAH STRUKTUR ALJABAR DI STKIP PGRI SITUBONDO - Tri Astindari; Ida Fitriana Ambarsari; Nur Hasanah; Aenor Rofek; Romlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate the effect of study habits and learning independence on students’ critical thinking skills in the Algebra Structure course at STKIP PGRI Situbondo using a quantitative method. The respondents were 4th-semester students of the Mathematics Education study program in the 2024/2025 academic year. Data were collected through questionnaires and tests, then analyzed using multiple regression. The results showed that the study habits variable was reliable, while the learning independence variable was  reliable. The average critical thinking skill of students was in the high category (84.33). The obtained multiple regression equation was Y = 15.511 + 0.125X₁ + 0.891X₂ with a coefficient of determination (R²) of 0.180. The significance test yielded a Sig. value of 0.410 > 0.05, indicating that study habits and learning independence did not have a significant effect on critical thinking skills. This study suggests that the improvement of students’ critical thinking skills is influenced by other factors beyond study habits and learning independence.